Analysis of End-to-End Delay Video Conferencing Services on a Mobile Ad Hoc Network - Riklan Kango; Nurwahidah Jamal; Mohamad Ilyas Abas (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
The purpose of this study is to conduct a series of tests on each increase in the number of node-clients on the Mobile Ad hoc Network, while each node performs real-time video conferencing services from the internet cloud which can have a significant impact on the Quality of Service. The quality of service of the Mobile Ad hoc Network that supports video conferencing in real-time is evaluated based on End-to-End Delay. The model offered is in the form of the implementation of an ad hoc network on the zoom cloud meeting service. We assessed the transmission scenario of wireless video conferencing services while changing the number of user nodes. It carried the measurement out 5 times and calculated the average value obtained to be compared against the number of different nodes in this case the data obtained using Wireshark software. The results showed that the end-to-end delay value on the Mobile Ad hoc Network increased by 27% when the scalability of the Mobile Ad hoc network was increased from 2 nodes to 4 nodes. Our proposed model can be helpful in making decisions about aspects of the number of nodes in the Mobile Ad hoc network in real-time communication